TINDAK KOMUNIKASI PEMBELAJARAN DI SEKOLAH DASAR - Widodo, Wahyu; Rozhana, Kardiana Metha (Universitas Nusantara PGRI Kediri, 2018)
The objective of the study is to describe the form of learning communication in the classroom and the meaning of the students to the learning communication on verbal, non-verbal, interpersonal, group, and public communication. The research used qualitative approach with phenomenology study design. The result of the research is the expression of thoughts and feelings of students to verbal communication is easy to understand the material and dare to ask. The expression of students' thoughts and feelings toward non-verbal communication is fear when teachers speak with high intonation, but students feel happy and feel loved by the teacher's touch. Expression of thoughts and feelings of students to interpersonal communication is a feeling of fun when teachers ask news, the state of self, health, birthday celebrations, and attention when experiencing bullying. Expression of thoughts and feelings of students to group communication is a feeling of fun when learning groups, feelings of freedom to discuss and ask the task personally to the teacher and discipline when grouping students who are busy in the classroom to be advised teachers. Expression of thoughts and feelings of students to public communication is easy to understand the subject matter and feelings of pleasure when inserted humor in the lecture method. Keywords: students' meaning, instructional communication, elementary school